(3JHjf GdbOQ ddjdI GdbOQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi efM GdYHGO djdI GdbOQ hHYO agPG JYdjb SejJg JHjjf GdbOQ ddjdI GdbOQ hQJHJg Ydi KeGfjI CHhGH GdChd ai PcQ eG hQO ef GeGQJgG s
(3BNQgG (B:s
(3hbO PcQ Gddg JYGdi gPg GddjdI ai ShQJgG KdGK eQGJ aGVQH KdGKI ai JSYI jcf SHYI hYTQjf Ydi Gfg jOd Ydi Pdc GdcJGH hGdSfI hPcQgeG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs